Experimental and clinical metastasis : a comprehensive review - Burnier, Jr., Miguel N.; Burnier, Julia V. (Springer New York, 2013)
The primary cause of death related to cancers can be traced back to metastases, originated from cancer cells. The presence of metastatic disease, the spread of cancer cells, is the most important prognostic and survival factor in patients with cancer. Although treatment of the primary tumor is well established and usually results in local control, treating metastatic disease is a much more daunting task. At diagnosis, few patients present with clinically detectable metastatic lesions regardless of the clinical prognostic factor. Clinical trials assessing potential therapeutic agents are important in order to define the best specific treatment for a particular patient, which are the basis for patient-oriented research that eventually lead to personalized medicine. This volume aims to comprehensively present the latest research and information about metastasis. Understanding the mechanisms underlying the metastatic phenomenon could have vast implications for the large number of patients who are at a high risk for the development of metastasis.